The impact of concentrations of inorganic salts to compromise in rooting branches Genuine apples and apple architecture in vitro - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
Took apple branches Genuine and Architecture tissue cultured in vitro 3 cm long and planted in the middle of food MS that contains different concentrations of inorganic salts and of Mntmat free growth and incubated Transplanter to study their effect on rooting Aalavra